General Practitioners' intention to prescribe and prescribing patterns in selected European settings: The OTCSOCIOMED project - Tsiantou, Vasiliki; Moschandreas, Joanna; Bertsias, Antonis; Papadakaki, Maria; Saridaki, Aristoula; Agius, Dominic; Alper, Zuleyha; Faresjo, Tomas; Klimkova, Martina; Martinez, Luc; Samoutis, George; Vlček, Jiří; et al. (Health policy, 2015)
The aim of this paper is to explore general practitioners' (GPs) prescribing intentions and patterns across different European regions using the Theory of Planned Behavior (TPB). A cross-sectional study was undertaken in selected geographically defined Primary Health Care areas in Cyprus, Czech Republic (CZ), France, Greece, Malta, Sweden and Turkey. Face-to-face interviews were conducted using a TPB-based questionnaire. The number of GP participants ranged from 39 to 145 per country. Possible associations between TPB direct measures (attitudes, subjective norms (SN) and perceived behavioral control (PBC)) and intention to prescribe were assessed by country. On average, GPs thought positively of, and claimed to be in control of, prescribing. Correlations between TPB explanatory measures and prescribing intention were weak, with TPB direct measures explaining about 25% of the variance in intention to prescribe in Malta and CZ but only between 3% and 5% in Greece, Sweden and Turkey. SN appeared influential in GPs from Malta; attitude and PBC were statistically significant in GPs from CZ. GPs' prescribing intentions and patterns differed across participating countries, indicating that country-specific interventions are likely to be appropriate. Irrational prescribing behaviors were more apparent in the countries where an integrated primary care system has still not been fully developed and policies promoting the rational use of medicines are lacking. Demand-side measures aimed at modifying GPs prescribing behavior are deemed necessary.
Keywords: dospělí; lékařská praxe - způsoby provádění; Švédsko; průzkumy a dotazníky; Cyprus; Female; Adult; ženské pohlaví; Greece; Surveys and Questionnaires; lidé; praktičtí lékaři; Francie; Turkey; Malta; úmysl; Turecko; Male; Sweden; Czech Republic; Intention; France; Česká republika; Kypr; lidé středního věku; mužské pohlaví; General Practitioners; Middle Aged; Řecko; Practice Patterns, Physicians'; Humans